Cadiolides J–M, antibacterial polyphenyl butenolides from the Korean tunicate Pseudodistoma antinboja. Issue 3 (1st February 2017) - Wang, Weihong; Kim, Hiyoung; Patil, Rahul S.; Giri, Awadut G.; Won, Dong Hwan; Hahn, Dongyup; Sung, Youjung; Lee, Jusung; Choi, Hyukjae; Nam, Sang-Jip; Kang, Heonjoong
Graphical abstract: Abstract: Activity-guided fractionations of the tunicate Pseudodistoma antinboja yielded four new compounds of the cadiolide class (cadiolides J–M, 1, 3 –5 ) along with a known one (cadiolide H, 2 ). The structures were defined by spectroscopic methods including X-ray crystallographic analysis. These compounds were evaluated for their antibacterial activity and exhibited potent antibacterial activity against all of the drug resistant strains tested with MICs comparable to those of marketed drugs such as vancomycin and linezolid.